The development of Canva-based e-modules in the subject of fundamentals of agribusiness plants for the agribusiness plants major of class X students at SMK Negeri 3 Sidenreng Rappang - Muhammad Rizal; Suardi Zain; Muhammad Aksan; Jusman Tang (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to develop a Canva-based e-module for the subject of Basic Plant Agribusiness in Grade X at SMK Negeri 3 Sidenreng Rappang and to examine its validity, practicality, and effectiveness. The research employed a Research and Development (R&D) method using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 15 students from the Agribusiness of Food Crops major. Research instruments included validation sheets, student response questionnaires, and pretest-posttest evaluations. The results showed that the developed e-module obtained a feasibility score of 80% from the material expert and 74.2% from the media expert, categorized as very feasible and feasible, respectively. Practicality tests conducted by students yielded average scores ranging from 78% to 94%, indicating the module was highly practical and usable without revision. The effectiveness test, based on comparisons of pretest and posttest scores, demonstrated an improvement in learning outcomes, indicating that the e-module effectively enhances students’ understanding of the material. Therefore, the Canva-based e-module is considered valid, practical, and effective as a learning medium to improve the quality of agribusiness education.